An Analytical Two Resistance Mass Transfer Model for Dye Adsorption on Bagasse Pith - Mckay, Gordon; El-Geundi, Mohammad S.; Abdul Wahab, M. Z.; Nassar, Mamdouh M. (1990)
The adsorption of fOUr dyes, namely, Basic Blue 69, Basic Red 22, Acid Blue 25 and Acid Red 114, onto bagasse pith has been studied. A mass transfer model, based on external mass transport and p01-e diffusion, has been used to correlate experimental and theoretical concentration versus time data. The model is an analytical solution which may be applied to adsorption systems in which the operating line and tie lines all terminate on the saturation plateau of the equilibrium isothenn. A single external mass transfer coefficient and a single p01'e diffusion coefficient were sufficient to describe each sytem fOT several initial dye concentrations and several pith masses. The external coefficient were 9.0 x 1(F3, 8.0 x 1(F3, 1.0 x 1(F3 and 1.5 x 10J cm S·I, the pOTe diffusivities were 5.5 x 1(F", 2.5 x 1(F", 2.2 x 1(F7 and 4.5 x l(Fi cm2 S·l for Basic Blue 69, Basic Red 22, Acid Blue 25 and Acid Red 114, respectively.